1994
DOI: 10.3109/10428199409051693
|View full text |Cite
|
Sign up to set email alerts
|

Trisomy 12 in Chronic Lymphocytic Leukemia and Hairy Cell Leukemia: A Cytogenetic and Interphase Cytogenetic Study

Abstract: Fluorescent in situ hybridization (FISH) with a chromosome 12-specific pericentromeric probe was performed in 42 patients with B-cell chronic lymphocytic leukemia (CLL) and in 10 patients with hairy cell leukemia (HCL). In all cases, a normal karyotype in more than 10 metaphase cells was obtained by conventional chromosome study. FISH documented that 6/42 patients with CLL in fact had trisomy 12 in 15-49% interphase cells. Sequential FISH studies were performed in 2 cases, showing an increase of percentage of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

1995
1995
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…[12][13][14][15][16][17][18][19][20] Auer et al and Hjalmar et al found the acquisition of trisomy 12 in none of 41 and 2 of 77 CLL cases. 15,16 Chevalier et al observed additional genomic aberrations with an extended probe set, in 13/31 (42%) CLL cases after a median time of 83 months.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[12][13][14][15][16][17][18][19][20] Auer et al and Hjalmar et al found the acquisition of trisomy 12 in none of 41 and 2 of 77 CLL cases. 15,16 Chevalier et al observed additional genomic aberrations with an extended probe set, in 13/31 (42%) CLL cases after a median time of 83 months.…”
mentioning
confidence: 99%
“…[8][9][10][11] However, only limited data are available from FISH studies of interphase cells, a more sensitive method for the detection of genomic aberrations in CLL. [12][13][14][15][16][17][18][19][20] 15,16 Chevalier et al observed additional genomic aberrations with an extended probe set, in 13/31 (42%) CLL cases after a median time of 83 months. 17 There was no association between clonal evolution and CD38 expression or disease progression but the acquisition of del(17p13) was associated with death in 7/11 cases.…”
mentioning
confidence: 99%
“…A high proportion of p53 gene deletion has been found in HCL and vHCL [16]. Trisomy 12 has also been demonstrated in HCL and vHCL [16,17]. In vHCL loss of chromosomes 2, 3, 4, 6, 10, 19, 21 and X have been demonstrated.…”
Section: Immunophenotype Of Hcl Vhcl and Slvlmentioning
confidence: 91%
“…The karyotypic studies therefore indicate that 5q13.3 harbors a candidate gene involved in the malignant transformation of HCL, possibly a tumor suppressor gene as deletions are commonly observed (Haglund et al, 1994). Several chromosome abnormalities have previously been observed in HCL (Golomb et al, 1978a,b;Berger et al, 1985;Brito-Babapulle et al, 1986;Nacheva et al, 1992;Juliusson et al, 1993;Lewis et al, 1993;Cuneo et al, 1994;Dö hner et al, 1994;Kluin-Nelemans, 1994). Until now, however, there has been no report which defines the location of a putative HCL-specific tumor suppressor gene.…”
Section: Introductionmentioning
confidence: 99%